2017
DOI: 10.3390/en10040559
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Control Ancillary Service Provided by Efficient Power Plants Integrated in Queuing-Controlled Domestic Water Heaters

Abstract: Abstract:Frequency is an important parameter of a power system. It is of great significance to maintain its stability, especially in the current development scenario of large-scale interconnected power systems. Thermostatically controlled appliances (TCAs) are good controllable resources for demand response owing to their rapid response capabilities and relatively wide controllable ranges. In this study, domestic water heaters, which have wider deadbands compared with other typical TCAs, such as heat pumps, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The paper included a systematic sizing procedure for such a home-based hybrid energy storage system and modeled it with a co-simulation framework for building energy use and electric power flow in distribution systems. In previous research, EWHs were used to regulate the frequency in an electric power distribution system [30]. Another research study showed that the aggregated EWH load can be controlled to contribute to shifting the system peak load [31].…”
Section: Introductionmentioning
confidence: 99%
“…The paper included a systematic sizing procedure for such a home-based hybrid energy storage system and modeled it with a co-simulation framework for building energy use and electric power flow in distribution systems. In previous research, EWHs were used to regulate the frequency in an electric power distribution system [30]. Another research study showed that the aggregated EWH load can be controlled to contribute to shifting the system peak load [31].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, load-frequency control focuses on mitigating the effects of unpredictable changes both in the demand and in the generation units that can address frequency deviations [2]. In fact, power imbalances between generation and consumption cause frequency variations [3]. In Europe, frequency control has a hierarchical structure, usually organized in up to five layers (from fast to slow timescales): (i) frequency containment (also known as primary frequency control); (ii) imbalance netting; (iii) automatic and/or manual frequency restoration (also known as secondary frequency control), and (iv) replacement [4].…”
Section: Introductionmentioning
confidence: 99%
“…This work contributes to the existing literature by providing a comprehensive analytical model and steady-state calculations for frequency regulation of a power system including DR and VSG controls. Most of the available literature either considers DR [10,[14][15][16][17][18][19][20][21]38,39] or virtual inertia [33,[35][36][37]40] for the purpose of frequency control. The literature (e.g., [41,42]) that considers the presence of both has one or more of the following limitations: frequency regulation is not considered, simulation results for a specific case are provided instead of a general model of the power system, and the formulation for steady-state error is not provided.…”
mentioning
confidence: 99%